Cytotoxicity Comparison of Harvard Zinc Phosphate Cement Versus Panavia F2 and Rely X Plus Resin Cements on Rat L929-fibroblasts - Mahasti, Sahabi (Royan Institute, 2011)
OBJECTIVE: Resin cements, regardless of their biocompatibility, have been widely used in restorative dentistry during the recent years. These cements contain hydroxy ethyl methacrylate (HEMA) molecules which are claimed to penetrate into dentinal tubules and may affect dental pulp. Since tooth preparation for metal ceramic restorations involves a large surface of the tooth, cytotoxicity of these cements would be more important in fixed prosthodontic treatments. The purpose of this study was to compare the cytotoxicity of two resin cements (Panavia F2 and Rely X Plus) versus zinc phosphate cement (Harvard) using rat L929-fibroblasts in vitro. MATERIALS AND METHODS: In this experimental study, ninety hollow glass cylinders (internal diameter 5-mm, height 2-mm) were made and divided into three groups. Each group was filled with one of three experimental cements; Harvard Zinc Phosphate cement, Panavia F2 resin cement and Rely X Plus resin cement. L929- Fibroblast were passaged and subsequently cultured in 6-well plates of 5×10(5) cells each. The culture medium was RPMI_ 1640. All samples were incubated in CO(2). Using enzyme-linked immune-sorbent assay (ELISA) and (3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) (MTT) assay, the cytotoxicity of the cements was investigated at 1 hour, 24 hours and one week post exposure. Statistical analyses were performed via two-way ANOVA and honestly significant difference (HSD) Tukey tests. RESULTS: This study revealed significant differences between the three cements at the different time intervals. Harvard cement displayed the greatest cytotoxicity at all three intervals. After 1 hour Panavia F2 showed the next greatest cytotoxicity, but after 24-hours and oneweek intervals Rely X Plus showed the next greatest cytotoxicity. The results further showed that cytotoxicity decreased significantly in the Panavia F2 group with time (p<0.005), cytotoxicity increased significantly in the Rely X Plus group with time (p<0.001), and the Harvard cement group failed to showed no noticeable change in cytotoxicity with time. CONCLUSION: Although this study has limitations, it provides evidence that Harvard zinc phosphate cement is the most cytotoxic product and Panavia F2 appears to be the least cytotoxic cement over time.